The cell cycle inhibitor RB is diluted in G1 and contributes to controlling cell size in the mouse liver - Zhang, Shuyuan; Zatulovskiy, Evgeny; Arand, Julia; Sage, Julien; Skotheim, Jan M. (Frontiers in Cell and Developmental Biology, 2022)
Every type of cell in an animal maintains a specific size, which likely contributes to its ability to perform its physiological functions. While some cell size control mechanisms are beginning to be elucidated through studies of cultured cells, it is unclear if and how such mechanisms control cell size in an animal. For example, it was recently shown that RB, the retinoblastoma protein, was diluted by cell growth in G1 to promote size-dependence of the G1/S transition. However, it remains unclear to what extent the RB-dilution mechanism controls cell size in an animal. We therefore examined the contribution of RB-dilution to cell size control in the mouse liver. Consistent with the RB-dilution model, genetic perturbations decreasing RB protein concentrations through inducible shRNA expression or through liver-specific Rb1 knockout reduced hepatocyte size, while perturbations increasing RB protein concentrations in an Fah-/- mouse model increased hepatocyte size. Moreover, RB concentration reflects cell size in G1 as it is lower in larger G1 hepatocytes. In contrast, concentrations of the cell cycle activators Cyclin D1 and E2f1 were relatively constant. Lastly, loss of Rb1 weakened cell size control, i.e., reduced the inverse correlation between how much cells grew in G1 and how large they were at birth. Taken together, our results show that an RB-dilution mechanism contributes to cell size control in the mouse liver by linking cell growth to the G1/S transition.